2022
DOI: 10.3389/fpls.2022.1017554
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of warming and nitrogen addition on the performance and competitiveness of invasive Solidago canadensis L.

Abstract: Changes in temperature and nitrogen (N) deposition determine the growth and competitive dominance of both invasive and native plants. However, a paucity of experimental evidence limits understanding of how these changes influence plant invasion. Therefore, we conducted a greenhouse experiment in which invasive Solidago canadensis L. was planted in mixed culture with native Artemisia argyi Levl. et Van under combined conditions of warming and N addition. Our results show that due to the strong positive effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Some studies have shown that the invasive plant Alternanthera philoxeroides increases its biomass due to a lack of natural enemy control after entering a new habitat, reducing defense investment and increasing investment in growth and reproduction, thereby enhancing its competitiveness (Geng, 2013). Furthermore, the evolutionary reduced competitive ability hypothesis proposes that if there is less competition within the scope of invasion and the competition involves the characteristics of adaptive cost, the invasive species will choose the aspects that may have adverse effects on them to evolve, thus reducing intraspecific interaction (Wolfe et al, 2004;Ren, 2020). The new association hypothesis states that the invasive species forms a new relationship with the species in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the invasive plant Alternanthera philoxeroides increases its biomass due to a lack of natural enemy control after entering a new habitat, reducing defense investment and increasing investment in growth and reproduction, thereby enhancing its competitiveness (Geng, 2013). Furthermore, the evolutionary reduced competitive ability hypothesis proposes that if there is less competition within the scope of invasion and the competition involves the characteristics of adaptive cost, the invasive species will choose the aspects that may have adverse effects on them to evolve, thus reducing intraspecific interaction (Wolfe et al, 2004;Ren, 2020). The new association hypothesis states that the invasive species forms a new relationship with the species in the community.…”
Section: Introductionmentioning
confidence: 99%
“…In invasive areas, due to the lack of natural enemies, resources originally used for defense can be used for growth and reproduction, improving their competitiveness [10][11][12]. The evolutionarily reduced competitive ability suggests that if there is less competition in invasive areas and competition involves adaptive cost characteristics, invasive species may evolve in a direction that has adverse effects on them, reducing intraspecies interactions [13,14]. The biotic resistance of competitors suggests that in new environments, exotic plants compete with local or other exotic plants to prevent their invasion by inhibiting their settlement, domestication, and persistence through competition for nutrients, water, light, and other resources [15,16].…”
Section: Introductionmentioning
confidence: 99%